Exploring the impact of flow dynamics on corrosive biofilms under simulated deep-sea high-pressure conditions using bio-electrochemostasis - Ivanovich, Nicolò; Marsili, Enrico; Shen, Xinhui; Messinese, Elena; Marcos,; Rajala, Pauliina; Lauro, Federico M. (Frontiers in Microbiology, 2025)
The formation of biofilms on metal surfaces contributes to the degradation of metallic materials through a process known as microbially influenced corrosion (MIC). While MIC accounts for a substantial portion of the global corrosion-related costs, its study is particularly challenging when related to infrastructure deployed in extreme environments inhabited by microorganisms, such as the deep sea. Here, this limitation was addressed with the development of a high-pressure bio-electrochemostat able to simulate the conditions of the deep sea more accurately than the traditional closed-batch setups. With this device, the corrosive capabilities of the piezophilic sulfate-reducing bacterium (SRB) Pseudodesulfovibrio profundus were analyzed at 0.1 (atmospheric pressure) and 30 MPa under flow and static conditions on AH36 marine-grade carbon steel. The results highlighted the device’s ability to closely replicate environmental conditions, thereby keeping bacterial communities metabolically active throughout the experiments and allowing for a more accurate assessment of the impact of MIC. Furthermore, the comparison between atmospheric and high hydrostatic pressures clearly showed that MIC represents a threat for metallic structures at the bottom of the ocean as much as at surface level.